EFFECTIVENESS OF STUDENT WORKSHEET ORIENTED ON THE GUIDED DISCOVERY LEARNING USING MIND MAPPING TO FACILITATE STUDENTS’ SCIENCE PROCESS SKILLS - Zuhriyah, Lathifatuz; Widodo, Wahono (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2019)
This study aims to describe the effectiveness of student worksheet oriented on the guided discovery learning using mind mapping to facilitate student’s science process skills. The data collection method was obtained from the test method with the type of one group pretest posttest design research. The study was conducted in class VIII-B MTsN Gresik with 30 students. The results showed as many as 27 students received n-gain scores in the high category and 3 students received n-gain scores in the medium category. In this study, it can be concluded that the student worksheet oriented guided discovery learning uses mind mapping to facilitate students' science process skills declared feasible in terms of effectiveness based on the science process skills test data, each student has a high category and the improvement science process skills indicator data that has a high category.Kata Kunci: worksheet, guided discovery, mind mapping, science process skills